Comment on: Conventional and biologic disease-modifying anti-rheumatic drugs for osteoarthritis: a meta-analysis of randomized controlled trials: Reply - Persson, Monica S.M.; Sarmanova, Aliya; Doherty, Michael; Zhang, Weiya (Oxford University Press, 2018)
MD reports a grant from AstraZeneca funding a non-drug PI-led study in Nottingham (Sons of Gout study) and honoraria for Advisory boards on osteoarthritis and gout for AstraZeneca, Grunenthal, Mallinckrodt, and Roche, outside the submitted work. WZ reports honoraria for Grunenthal and speaker fees for Bioiberica and Hisun, outside the submitted work. All other authors have declared no conflicts of interest.